Electrochemically Modulated Nitric Oxide (NO) Releasing Biomedical Devices via Copper(II)-Tri(2-pyridylmethyl)amine Mediated Reduction of Nitrite - Ren, Hang (American Chemical Society, 2014)
[Image: see text] A controllable and inexpensive electrochemical nitric oxide (NO) release system is demonstrated to improve hemocompatibility and reduce bacterial biofilm formation on biomedical devices. Nitric oxide is produced from the electrochemical reduction of nitrite using a copper(II)-tri(2-pyridylmethyl)amine (Cu(II)TPMA) complex as a mediator, and the temporal profile of NO release can be modulated readily by applying different cathodic potentials. Single lumen and dual lumen silicone rubber catheters are employed as initial model biomedical devices incorporating this novel NO release approach. The modified catheters can release a steady, physiologically-relevant flux of NO for more than 7 days. Both single and dual lumen catheters with continuous NO release exhibit greatly reduced thrombus formation on their surfaces after short-term 7-h intravascular placement in rabbit veins (p < 0.02, n = 6). Three day in vitro antimicrobial experiments, in which the catheters are “turned on” for only 3 h of NO release each day, exhibit more than a 100-fold decrease in the amount of surface attached live bacteria (n = 5). These results suggest that this electrochemical NO generation system could provide a robust and highly effective new approach to improving the thromboresistance and antimicrobial properties of intravascular catheters and potentially other biomedical devices.